Cross-cultural measurement invariance evidence of individualism and collectivism: from the idiosyncratic to universal - Soler-Anguiano, Francisco Leonardo; Rivera-Aragón, Sofía; Díaz-Loving, Rolando (Frontiers in Psychology, 2023)
The Mexican Horizontal and Vertical Individualism and Collectivism Scale was created to address the lack of adequate psychometric properties when assessing individualism and collectivism in Spanish-speaking cultures. This scale has shown adequate model fit and reliability in Mexico as a Spanish-speaking culture. However, the scale has yet to be translated, adapted, or assessed in other cultures. We propose that the lack of adequate psychometric properties of the scales commonly used to assess the construct at the individual level is due to a combination of orientations in terms of construct focus operationalization and an absence of an idiosyncratic perspective. Hence, this study aims to translate and adapt the Mexican Horizontal and Vertical Individualism and Collectivism Scale into English, test its subsequent psychometric properties, and assess its cross-cultural measurement invariance between the United States and Mexico. The scale showed optimal internal consistency. Furthermore, confirmatory factor analyses lend support to the original theoretical model, affirming the structural validity of the scale. Cross-cultural measurement invariance between equivalence measurement indices indicates that the cross-cultural replicability properties of the Mexican Horizontal and Vertical Individualism and Collectivism Scale in the United States and Mexico are generally acceptable.